Neutrophil Extracellular Traps in Arterial and Venous Thrombosis - Laridan, Elodie; Martinod, Kimberly; De Meyer, Simon F. (Seminars in Thrombosis and Hemostasis, 2019)
Thrombotic complications are still a major health risk worldwide. Our view on the pathophysiology of thrombosis has significantly changed since the discovery of neutrophil extracellular traps (NETs) and their prothrombotic characteristics. Generated by neutrophils that release their decondensed chromatin as a network of extracellular fibers, NETs promote thrombus formation by serving as a scaffold that activates platelets and coagulation. The thrombogenic involvement of NETs has been described in various settings of thrombosis, including stroke, myocardial infarction, and deep vein thrombosis. The aim of this review is to summarize existing evidence showing the presence of NETs in human thrombus material. Following an introduction on NETs and their role in thrombus formation, the authors address studies showing the presence of NETs in arterial or venous thrombi. In addition, they focus on potential novel therapeutic opportunities to resolve or prevent thrombosis by targeting NETs.
Keywords: NETs; thrombosis; neutrophil; stroke; venous thromboembolism; myocardial infarction